2015
DOI: 10.1093/molbev/msv144
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Trade-Offs Determine the Role of the Molecular Chaperonin GroEL in Buffering Mutations

Abstract: Molecular chaperones fold many proteins and their mutated versions in a cell and can sometimes buffer the phenotypic effect of mutations that affect protein folding. Unanswered questions about this buffering include the nature of its mechanism, its influence on the genetic variation of a population, the fitness trade-offs constraining this mechanism, and its role in expediting evolution. Answering these questions is fundamental to understand the contribution of buffering to increase genetic variation and ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 64 publications
3
60
0
Order By: Relevance
“…One apparent coping mechanism is the constitutive overexpression of protein chaperonins and heat shock proteins by symbionts. Chaperonins in free-living bacteria buffer enzyme function against the effects of environmental extremes, oxidative stress, and genetic drift, which are major forces shaping symbiont genome evolution ( Williams et al 2010 ; McCutcheon and Moran 2012 ; Sabater-Muñoz et al 2015 ). In bacterial symbionts, chaperonins likely aid in the proper folding of proteins debilitated by the accumulation of deleterious mutations ( Moran 1996 ; Fares et al 2004 ; Kupper et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One apparent coping mechanism is the constitutive overexpression of protein chaperonins and heat shock proteins by symbionts. Chaperonins in free-living bacteria buffer enzyme function against the effects of environmental extremes, oxidative stress, and genetic drift, which are major forces shaping symbiont genome evolution ( Williams et al 2010 ; McCutcheon and Moran 2012 ; Sabater-Muñoz et al 2015 ). In bacterial symbionts, chaperonins likely aid in the proper folding of proteins debilitated by the accumulation of deleterious mutations ( Moran 1996 ; Fares et al 2004 ; Kupper et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, high constitutive expression of GroESL is likely costly to hosts. It is known to be highly expressed as protein in pea aphids, requiring extensive cellular resources ( Baumann et al 1996 ; Sabater-Muñoz et al 2015 ). Furthermore, it may also impose ecological constraints on plant–insect interactions.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case for the chaperone GroEL, a protein that is overexpressed in endosymbiotic bacteria and seems to participate in the correct folding of many damaged proteins, thus buffering the effect of slightly deleterious mutations . In fact, a number of elegant experiments carried out in Escherichia coli have shown that overexpression of GroEL in bacteria evolving under continuous bottleneck, and thus with a strong genetic drift, can avoid extinction or rescue bacterial cells …”
Section: Genome Reduction In Endosymbionts: Gene Lossmentioning
confidence: 99%
“…Moreover, accumulating evidence suggests that the function of chaperones has important consequences for robustness (Queitsch et al. 2002) and adaptation to high mutational load (Sabater-Muñoz et al. 2015).…”
Section: Introductionmentioning
confidence: 99%